2008
DOI: 10.1007/s00404-008-0718-0
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent mucinous cystadenoma: a laparoscopic approach

Abstract: The second most common epithelial tumor of the ovary is mucinous-type, and it constitutes 8-10% of all ovarian tumors. The recurrence of mucinous cystadenoma is very rare after complete excision. Only four such cases have been reported till date. The case presented in this report is the fifth, who had her initial surgery performed by gynecologic oncology team by laparotomy and was followed up by the same group. After recurrence at the same ovary, the patient underwent laparoscopic evaluation and unilateral sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Few cases have been reported regarding recurrent benign mucinous cystadenoma of the ovary. [10][11][12][13][14][15][16] However, in 2010, Ben-Ami et al 17 reported that the recurrence rates of cystadenomas may not be as low as reported in the literature. They showed that three of 42 patients (7.1%) included in their study had mucinous cyst recurrence in the ipsilateral ovary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few cases have been reported regarding recurrent benign mucinous cystadenoma of the ovary. [10][11][12][13][14][15][16] However, in 2010, Ben-Ami et al 17 reported that the recurrence rates of cystadenomas may not be as low as reported in the literature. They showed that three of 42 patients (7.1%) included in their study had mucinous cyst recurrence in the ipsilateral ovary.…”
Section: Discussionmentioning
confidence: 99%
“…The recurrence of ovarian mucinous cysts is very rare. Few cases have been reported regarding recurrent benign mucinous cystadenoma of the ovary 10–16 . However, in 2010, Ben‐Ami et al 17 reported that the recurrence rates of cystadenomas may not be as low as reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Turkyilmaz et al in 2009 reported a case that had her initial surgery performed by gynecologic oncology team by laparotomy and was followed up by the same group. After recurrence at the same ovary, the patient underwent laparoscopic evaluation and unilateral salpingo-oophorectomy was performed [6].…”
Section: Discussionmentioning
confidence: 99%
“…Most mucinous ovarian neoplasms (77-87%) are classified as benign. These neoplasms tend to be cystic in nature, and the majority of mucinous tumors (76%) are multilocular, whereas 24% are unilocular ( Turkyilmaz et al ., 2009 ). In summary, a minimally invasive surgical approach by laparoscopy with preservation of both ovaries is feasible and crucial, even in rare and difficult cases such as the current case.…”
Section: Discussionmentioning
confidence: 99%